Circuito de coordinación en la conducción del balón en la sub-12 de la academia de fútbol femenino Innovagol” - Victor Hugo, Castro Cardoso (2020)
The present investigation project has as a goal, determinate how the coordination´s circuit influences in the conduction of the ball in the sub 12 female soccer academy “innovagol”. Having knowledge the coordination circuit, we can say it´s an entertainment that consist in realizing a group of exercises in different selected station and positioned around of a sport stage (normally spots field) that are followed in a fast sequence and these exercises can be with or without ball, meanwhile the conduction ball is transported to a zone of the pitch and other using different circuit´s coordination, with different parts of de foot, realizing successive touches and maintaining control over it, methodologically investigation has been used with an inductive method and deductive because we analyze, and the study central problem, and systematize the results obtained through an analysis across the causes and consequences directed to the development of technical bases, basic to soccer, the investigation was an explanatory type and descriptive, we determinate that the dates and characteristics of the variables was of field and transversal character, the population were the female soccer´s academy innovagol , the sample conformed by 50 athletes from 12 years, the used technique was observation and the instrument, pre file and post file´s observation, which we can compare that there is an improvement between the study variable since the coordination´s circuits help the ball´s conduction and strength the technical fundamentals of the female soccer´s academy “innovagol”.